Aid Dependence and the quality of governance : a cross-country empirical analysis - Knack, Stephen F. (Policy research working paper, 2000)
July 2000 - Do higher levels of aid erode the very quality of governance poor countries need for sustained and rapid income growth? Good governance-in the form of institutions that establish predictable, impartial, and consistently enforced rules for investors-is crucial for the sustained and rapid growth of per capita incomes in poor countries. Aid dependence can undermine institutional quality by weakening accountability, encouraging rent seeking and corruption, fomenting conflict over control of aid funds, siphoning off scarce talent from the bureaucracy, and alleviating pressures to reform inefficient policies and institutions. Knack's analyses of cross-country data provide evidence that higher aid levels erode the quality of governance, as measured by indexes of bureaucratic quality, corruption, and the rule of law. This negative relationship strengthens when instruments for aid are used to correct for potential reverse causality. It is robust to changes in the sample and to several alternative forms of estimation. Recent studies have concluded that aid's impact on economic growth and infant mortality is conditional on policy and institutional gaps. Knack's results indicate that the size of the institutional gap itself increases with aid levels. This paper-a product of Regulation and Competition Policy, Development Research Group-is part of a larger effort in the group to identify the determinants of good governance and institutions conducive to long-run economic development. The author may be contacted at sknack@worldbank.org